Whipple Disease: A Case Report - Pisco Martins, Catarina; Pinho Rocha, Francisca; Montezinho, Sara; Coelho, Edgar (Gazeta Médica, 2025)
Whipple disease is a rare multisystemic infection caused by the gram-positive bacillus Tropheryma whipplei. Diagnosis is difficult due to the nonspecific initial symptoms and its delay invariably affects the prognosis. This case highlights the importance of the family doctor's high index of suspicion and his role in the prompt diagnosis of a rare pathology. We present the case of a 66-year-old man initially evaluated in primary care for mandibular swelling. The diagnosis of Whipple's disease was made 2 months later, when new symptoms appeared, and the Family Doctor requested more targeted complementary diagnostic exams. Rapid coordination with hospital care in an urgent context proved to be an efficient weapon in approaching this clinical case, allowing quick initiation of antibiotic therapy, which consequently provided a favorable prognosis for the patient.